COMPLEX CARE FOR WOUNDS WITH A SERIOUS PROGNOSIS: PALLIATIVE CARE AND ETHICAL AND INTERDISCIPLINARY REFLECTIONS ON INEQUALITIES IN CARE - Louzakan Pereira Andrade, Douglas; Feitosa Rodrigues, Lutigard; Eduarda Batista Henriques, Maria; Borges Mesquita, Flávia; Maria de Azevedo, Lívia; Barros de Valmoré Fernandes, Marcelo; da Cruz Araruna Oliveira, Patrícia (Revista Gênero e Interdisciplinaridade, 2026)
Severe prognosis wounds represent a complex clinical condition that requires rapid, integrated, and humanized responses from healthcare teams. Often associated with infections, severe trauma, or chronic comorbidities, these lesions exceed the curative model and require early integration of palliative care. This narrative qualitative review analyzed eight scientific articles discussing clinical management, healthcare system limitations, and the importance of empathy and listening in caring for such patients. Despite the availability of effective therapeutic technologies, the absence of unified protocols, service fragmentation, and shortage of specialized professionals compromise care outcomes. Palliative care emerges as an ethical, person-centered approach, offering relief from suffering and fostering shared decisions. Strengthening multidisciplinary actions, investing in continuous education, and valuing emotional and social aspects of care are essential to transform current realities. This study reinforces the need for an integral and sensitive view of wounds that often expose more than physical illness they reveal social inequalities and institutional neglect.